2013
DOI: 10.1111/nup.12022
|View full text |Cite
|
Sign up to set email alerts
|

Beat the clock! Wait times and the production of ‘quality’ in emergency departments

Abstract: Emergency care in large urban hospitals across the country is in the midst of major redesign intended to deliver quality care through improved access, decreased wait times, and maximum efficiency. The central argument in this paper is that the conceptualization of quality including the documentary facts and figures produced to substantiate quality emergency care is socially organized within a powerful ruling discourse that inserts the interests of politics and economics into nurses' work. The Canadian Triage a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…Reducing waiting time and its impact on the treatment cost is another priority at the emergency department. Melon et al (2013) (26) found that increased patient waiting time at this department has affected treatment costs, and by designing appropriate strategies, patients' waiting time at the emergency department can be reduced.…”
mentioning
confidence: 99%
“…Reducing waiting time and its impact on the treatment cost is another priority at the emergency department. Melon et al (2013) (26) found that increased patient waiting time at this department has affected treatment costs, and by designing appropriate strategies, patients' waiting time at the emergency department can be reduced.…”
mentioning
confidence: 99%
“…Whereas queuing approaches aim to improve patient satisfaction, it also important to not sacrifice the quality of service, as highlighted by Melon et al . () and measured as the URR in our study. URR was adopted as the adequacy measure because it had uniform use after becoming the target goal for the US governmental Centers for Medicare and Medicaid Services pay‐for‐performance policy in 2011 (Tangri et al .…”
Section: Discussionmentioning
confidence: 97%
“…; Melon et al . ) with a focus on emergency departments, primary care clinics, cardiac care, and the adoption of lessons learned from hospitality management. Shan et al .…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Although IE has been taken up in studies of nursing and healthcare internationally (Melon et al 2013, Rankin 2003, 2009, Rankin and Campbell 2009 it is a relatively new method of inquiry for nurse researchers in the UK. Therefore it is also hoped that this paper will introduce IE as a useful method of inquiry to a new audience of nurse researchers interested in understanding how difficulties are produced in real life situations.…”
Section: Introductionmentioning
confidence: 99%